The Relationship of Waist Circumstances With Hypertension in Hutabarat Village Partali Toruan - Agustaria Ginting; Lindawati Simorangkir; Irma Dhevi Yanti Lubis (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
Hypertension is an increase in systolic and diastolic blood pressure, where systolic is more than 140 mmHg and diastolic is more than 90 mmHg. The prevalence of hypertension in the world's population is found to be 22% and has resulted in 23.7% of deaths from a total of 1.7 million deaths in Indonesia. Waist circumference is a measurement of the distribution of abdominal fat which has a close relationship with hypertension, the larger the waist circumference, the more fat deposits in the abdominal area, the more fat deposits, the more bad cholesterol which will make blood vessels narrow and can cause hypertension. This study aims to determine the relationship between waist circumference and hypertension at the age of 18-45 years in Hutabarat Partali Toruan Village in 2021. This type of research is analytic observational with a cross sectional design. The population as many as 2775 people with a total sample of 96 people who were taken by purposive sampling technique. Collecting data by means of interviews, and observations using metline (cm) for waist circumference and sphygmomanometer for blood pressure. Based on the results of the study, it was found that waist circumference was abnormal at 77.1%, and hypertension was 56.3%. The results of the chi square test obtained p-value = 0.017 (p <0.05), meaning that there is a relationship between waist circumference and the incidence of hypertension. It is hoped that the Public Health Center will provide health promotion about a healthy lifestyle such as improving diet, activity and exercise, getting enough rest, not smoking, not consuming alcohol.